Rivaroxaban as an Antithrombotic Agent in a Patient With ST-Segment Elevation Myocardial Infarction and Left Ventricular Thrombus - Rajeev Seecheran; Valmiki Seecheran MBBS; Sangeeta Persad MBBS; Naveen Anand Seecheran MBBS, MSc, FACC, FESC (SAGE Publishing, 2017)
The incidence of left ventricular (LV) thrombi in the setting of an anterior myocardial infarction has declined significantly since the advent of primary percutaneous coronary intervention coupled with contemporary antithrombotic strategies in ST-segment elevation myocardial infarctions (STE-ACS). Despite oral anticoagulation with the currently accepted, standard-of-care vitamin K antagonist, warfarin, major bleeding complications still arise. Rivaroxaban is a novel, direct oral factor X anticoagulant that has several advantageous properties, which can attenuate bleeding risk. We present a case in which a patient successfully underwent a 3-month course of rivaroxaban in addition to his dual antiplatelet regimen of aspirin and ticagrelor for his STE-ACS and LV thrombus with resultant complete dissolution.